2021
DOI: 10.21608/jcbr.2020.45551.1077
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficiency of parsley (Petroselinum crispum) against oxidative stress, DNA damage and nephrotoxicity induced with anti- tuberculosis drugs

Abstract: It is with great pleasure that I write this editorial to welcome you to the IJCBR. This journal provides a platform for publication of original and reviews research articles, short communications, letter to editor, thesis abstract, conference report, and case studies. These types of publication are directed at the interface of the fields of cancer and biomedical research.The IJCBR relies on a distinguished expert of the Advisory and Editorial Board Members from the top international league covering in depth th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous phytochemical analysis of Parsley revealed the presence of certain compounds such as flavonoids [40], carotenoids [41], ascorbic acid [42], and tocopherol [43]. These components of fresh Parsley leaves eliminate the superoxide anion in vitro and the hydroxyl radical, in addition to protecting against membrane oxidation induced by ascorbic acid [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous phytochemical analysis of Parsley revealed the presence of certain compounds such as flavonoids [40], carotenoids [41], ascorbic acid [42], and tocopherol [43]. These components of fresh Parsley leaves eliminate the superoxide anion in vitro and the hydroxyl radical, in addition to protecting against membrane oxidation induced by ascorbic acid [44].…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration of parsley is effective in reducing stress-induced gastric injury by supporting the cellular antioxidant defense system (Akıncı et al, 2017). Ashry et al (2021) demonstrated that parsley extract may be as promising as nephroprotection against isoniazid and rifampicin nephrotoxicity through their antioxidant and radical scavenging activities.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh-cut parsley (Petroselinum crispum (Mill.) Fuss), a ready-to-use ingredient or garnish for multiple dishes in home kitchens and restaurants, deserves interest for the beneficial effects that its main compounds exert on health [32][33][34]. It was chosen for this study because it is particularly rich in AA [31], and, compared to other minimally processed produce, it undergoes more rapid deterioration because of chopping, a mechanical wounding that causes a tremendous disruption of cells, inducing a release of nutrients, accelerating senescence and quality loss [4,10], enhancing bacterial growth [35] and, on the whole, strongly affecting its shelf-life.…”
Section: Introductionmentioning
confidence: 99%